(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The purpose of this scientific work is to factually examine how the rate of elevation of the Blended Learning and Digital Adaptive Tools during teaching ESP is affected by the development of digital tools in English classes for non philological audience. The scientific outcome employs correlation and board data analyses to explore the relationship between the variety of methods of modern century. The results indicate that as the digitalization show mark rises, the indication rate of both Blended Learning and D